Monitoring the scale-up of antiretroviral therapy programmes: methods to estimate coverage - Boerma J Ties; Stanecki Karen A; Newell Marie-Louise; Luo Chewe; Beusenberg Michel; Garnett Geoff P; Little Kirsty; Calleja Jesus Garcia; Crowley Siobhan; Kim Jim Yong; Zaniewski Elizabeth; Walker Neff; et al. (The World Health Organization, 2006)
This paper reviews the data sources and methods used to estimate the number of people on, and coverage of, antiretroviral therapy (ART) programmes in low- and middle-income countries and to monitor the progress towards the "3 by 5" target set by WHO and UNAIDS. We include a review of the data sources used to estimate the coverage of ART programmes as well as the efforts made to avoid double counting and over-reporting. The methods used to estimate the number of people in need of ART are described and expanded with estimates of treatment needs for children, both for ART and for cotrimoxazole prophylaxis. An estimated 6.5 million people were in need of treatment in low- and middle-income countries by the end of 2004, including 660 000 children under age 15 years. The mid-2005 estimate of 970 000 people receiving ART in low- and middle-income countries (with an uncertainty range 840 000-1 100 000) corresponds to a coverage of 15% of people in need of treatment.